Safety of Vaccination within First Year of Life-The Experience of One General Medicine Center - Claudia Felicia Pop; Petronela Coblisan; Ligia Capalna; Paraschiva Cherecheș Panța; Anca Dana Buzoianu; Ioana Corina Bocsan (MDPI AG, 2023)
Vaccines represent an important preventive strategy in paediatric populations, but the rate of vaccination has been constantly declining in the last decade. Concerns about vaccines' safety represent one of the main causes of vaccine hesitancy among parents. The aim of this study was the analysis of the immediate adverse reactions induced by vaccines included in the national program of immunization for the first year of life. Method: Eighty-one children born between 1st of January 2018 and 31st of March 2019 were included. The vaccination refusal rate, and incidence and severity of adverse effects induced by three mandatory vaccines (Hexavalent, Prevenar 13 and MMR) were analyzed. The level of parents' education and the sources of information that were consulted in order to understand the adverse effects were also analyzed. Results and conclusions: The rate of adverse events was lower than 30% of the total number of doses, and most of them were mild. The incidence and severity of vaccine-induced adverse effects were correlated with prematurity. The vaccine hesitancy rate was lower than the national one, possibly due to a high level of education and good information provided by doctors that might have led to parents' concerns regarding vaccination being answered.